Research on the Evolution of “Ren” and “Li” in SikuQuanshu Confucian Classics - Hu, Bo; Xing, Fugui; Fan, Miaorong; Zhu, Tingshao (Frontiers in Psychology, 2021)
Confucian culture has always been the most glorious component of Chinese culture. Governing the mainstream world of China for more than two millennia, it has cast a profound and long-lasting influence on the way of thinking and cultural-psychological formation of the Chinese people. Confucianism emphasizes caring about others with benevolence and governing a state with ethics, reflecting the importance of moral principles for politics. “Ren” and “Li” are important parts of the core values of Confucianism, so analyzing the differences between them and their evolution is of great significance for further understanding Confucian culture. This paper selected 132 classic Confucian works from SikuQuanshu, a large collection of books compiled during the Qianlong’s reign of the Qing Dynasty (1636–1912), to calculate the use of frequency of “Ren” and “Li” in those books by means of big data. Then the data was analyzed to show the development trajectory of “Ren” and “Li” from the Spring and Autumn period (770–476 BC) to the Qing Dynasty, providing a new perspective for the study of Confucian culture. The analysis result shows that from the Spring and Autumn period to the Qing Dynasty, both the frequencies of “Ren” and “Li” record a peak and a bottom: “Ren” has its peak in the Sui and Tang period(581–907) while “Li” reaches its climax in the Wei and Jin period(220–420); both “Ren” and “Li” hit their bottom during the Yuan Dynasty (1279–1368). The average frequency of “Li” is higher than that of “Ren” during most of the time (8 dynasties and periods). In general, “Li” is more frequently referred to in classic Confucian works than “Ren”, especially in those of the pre-Sui and Tang era. The An-Shi Disturbances in the Tang Dynasty marks an important turning point for the frequencies of “Ren” and “Li” in classic Confucian works.